2002
DOI: 10.1002/jmri.10190
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy with metabolite nulling reveals regional differences of macromolecules in normal human brain

Abstract: Purpose: To quantify the macromolecular content in different anatomic brain regions and to evaluate an age dependency of the macromolecular concentrations. Material and Methods:A short echo time Stimulated Echo Acquisition Mode (STEAM) sequence was used without and with inversion recovery metabolite nulling in 8 -12 healthy volunteers. Quantitation was achieved by an extended LCModel, and macromolecular resonances at 0.9, 1.4, 2.1, and 3.0 ppm were evaluated. Results:In the cerebellum, the 1.4, 2.1, and 3.0 pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 23 publications
3
51
3
1
Order By: Relevance
“…The latter is often preferred in recent publications (see, e.g., [126,63,140,141]). This can be explained by the fact that adding macromolecular profiles adds more prior knowledge [2] X X X QUEST [28] X X Elster et al's [38] X X TDFD Fit [85] X X X CFIT [3] X LCModel [18] X X X Young/Soher et al's [132,48,71] X X…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The latter is often preferred in recent publications (see, e.g., [126,63,140,141]). This can be explained by the fact that adding macromolecular profiles adds more prior knowledge [2] X X X QUEST [28] X X Elster et al's [38] X X TDFD Fit [85] X X X CFIT [3] X LCModel [18] X X X Young/Soher et al's [132,48,71] X X…”
Section: Discussionmentioning
confidence: 95%
“…However, recent studies [125][126][127] show that strong correlation between the macromolecular concentration/composition and the location of the voxel in the brain have been found. Hoffmann et al [125] also found significant correlation with age but not with gender, while no significant correlation with age could be detected by Mader et al [126] (the correlation with gender was not studied in the latter reference). Similarly, several conditions such as stroke [128], brain tumors [63] and multiple sclerosis [129] show an altered macromolecule profile.…”
Section: Macromolecular Signalsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, macromolecule contamination remains a challenge for accurate quantification of brain metabolites using short echo-time spectroscopy. Methods currently under development include using double inversion recovery for metabolite-nulling to obtain macromolecular spectra, which can be used for subtraction or as prior knowledge for fitting (Kassem and Bartha, 2003;Mader et al, 2002). Further validation may be needed to test efficiency of macromolecule removal using these methods.…”
Section: Discussionmentioning
confidence: 99%
“…This feature may be used either to suppress MM signal or to selectively acquire MM signal ("metabolite nulled spectra"). The latter approach proved to be a robust tool for the analysis of MM [11][12][13][14]. This information can be used e.g., for including MM signal into the model library of fitting routines in order to obtain a physically meaningful estimate of the baseline.…”
Section: Introductionmentioning
confidence: 99%